Value of PET/CT 3D visualization of head and neck squamous cell carcinoma extended to mandible. Issue 5 (May 2018) - Lopez, R.; Gantet, P.; Julian, A.; Hitzel, A.; Herbault-Barres, B.; Alshehri, S.; Payoux, P.
Abstract: Purpose: To study an original 3D visualization of head and neck squamous cell carcinoma extending to the mandible by using [18F]-NaF PET/CT and [18F]-FDG PET/CT imaging along with a new innovative FDG and NaF image analysis using dedicated software. The main interest of the 3D evaluation is to have a better visualization of bone extension in such cancers and that could also avoid unsatisfying surgical treatment later on. Patients and methods: A prospective study was carried out from November 2016 to September 2017. Twenty patients with head and neck squamous cell carcinoma extending to the mandible (stage 4 in the UICC classification) underwent [18F]-NaF and [18F]-FDG PET/CT. We compared the delineation of 3D quantification obtained with [18F]-NaF and [18F]-FDG PET/CT. In order to carry out this comparison, a method of visualisation and quantification of PET images was developed. This new approach was based on a process of quantification of radioactive activity within the mandibular bone that objectively defined the significant limits of this activity on PET images and on a 3D visualization. Furthermore, the spatial limits obtained by analysis of the PET/CT 3D images were compared to those obtained by histopathological examination of mandibular resection which confirmed intraosseous extension to the mandible. Results: The [18F]-NaF PET/CT imaging confirmed the mandibular extension in 85% of cases and was not shown in [18F]-FDG PET/CT imaging. The [18F]-NaF PET/CT was significantly more accurate than [18F]-FDG PET/CT in 3D assessment of intraosseous extension of head and neck squamous cell carcinoma. This new 3D information shows the importance in the imaging approach of cancers. All cases of mandibular extension suspected on [18F]-NaF PET/CT imaging were confirmed based on histopathological results as a reference. Conclusions: The [18F]-NaF PET/CT 3D visualization should be included in the pre-treatment workups of head and neck cancers. With the use of a dedicated software which enables objective delineation of radioactive activity within the bone, it gives a very encouraging results. The [18F]-FDG PET/CT appears insufficient to confirm mandibular extension. This new 3D simulation management is expected to avoid under treatment of patients with intraosseous mandibular extension of head and neck cancers. However, there is also a need for a further study that will compare the interest of PET/CT and PET/MRI in this indication.